'I Always Felt I Was Black': cannibalism, race, and desire in Tennessee Williams. Issue Volume 32:Issue10(2018) (26th November 2018) - Lossada, Alexandra Maria
ABSTRACT: This close reading of Tennessee Williams' 1946 short story 'Desire and the Black Masseur' and 1958 play Suddenly Last Summer joins a trend in scholarship examining race in Williams' work. Homosexuality and race are inextricably linked in these two texts, but scholarship often lacks a locus through which to discuss one issue without discounting the other. Therefore, I employ French psychoanalyst Jean Laplanche's Essays on Otherness to draw out problematic 'maternal figures': characters or spaces that embody 'ambivalence'. Such ambivalence refers to the condition of simultaneously nurturing and seducing (in this case) white, homosexual male bodies. I shall argue that homosexuality (cannibalistically extended) and race ('I always felt I was black') should be examined in relation to each other in 'Desire' and Suddenly. 'Desire' establishes 'ambivalence' by way of its theatre and bathhouse, locations taking human (and racial) form in the figure of the masseur. Hence, cannibalism not only constitutes the sexual climax of Anthony Burns and the masseur's relationship, but also becomes a 'pregnancy' via ingestion. In Suddenly, Violet and Catharine cannot separate their desires to nurture and seduce Sebastian, let alone articulate them. Such 'failure' leads Sebastian to seek an alternative, 'blackening' maternal source that ultimately 'aborts' him.